PRO DAN KONTRA SANKSI PEMISKINAN BAGI PELAKU TINDAK PIDANA KORUPSI DI INDONESIA (PRO AND CONTRA IMPROVERISHING PUNISHMENT TO CORRUPTOR IN INDONESIA) - TEMMY HASTIAN, S.H. NPM.A2021151027, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT Corruption is a crime that has been rooted in the life of the Indonesian nations, ranging from government, senator, to law enforcement. There has no doubt if people are very disturbby this crime. Many assumptions and discourses are expressed to give and as additional deterrent effect to the perpetrators, ranging from impoverishment to perpetrators of the Corruption Crime, as well as the death punishment. Corruption crimes is a crime that must be eradicated by an extraordinary way, it is because corruption harms for many people, corruption caused inhibits all development, both physical and non-physical development. Basically the trigger factor of a person committing a criminal act of corruption is one of greed, as stated in a previously written paper, and the main purpose of the perpetrator of corruption crimes is wealth, and in fact perpetrators of corruption crimes are afraid of poverty. The formulation of the issues to be discussed in this paper is